Analisis Sensitivitas Frame 2d Tipe Portal terhadap Variasi Geometri dan Kondisi Batas dengan SAP2000: Analysis of 2d Portal-Type Frames (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2026)
This study examines the stiffness sensitivity of 2D portal-type frames to variations in geometry and boundary conditions using finite element analysis in SAP2000. Structural stiffness plays a critical role in determining deformation responses and internal force distribution, particularly in portal systems that are highly influenced by changes in element dimensions and support restraints. The portal model is analyzed under vertical and horizontal distributed loads of 10 kN/m to evaluate shear forces, bending moments, axial forces, and displacements. The analysis shows that the maximum shear force reaches 7,086 kN at the base of the column, while the largest moment occurs at the fixed support with a value of 20,673 kN·m. The axial forces in both columns are dominated by compression and remain relatively constant along their height, reflecting the significant influence of vertical loading. The maximum lateral displacement is approximately 0.202 m, which remains within acceptable limits for sensitivity analysis but still requires consideration of drift criteria for real design applications. These findings indicate that small changes in geometry and boundary conditions can produce meaningful variations in structural response, highlighting the importance of sensitivity studies during early design stages to achieve a more efficient and stable structural configuration. Keywords: 2D frame, structural stiffness, boundary conditions, SAP2000
Keywords: 2D Frame; Boundary Conditions; Structural Stiffness; SAP2000